Die. 2, Split the party - Gillen, Kieron (Image Comics, 2020)
"No one can escape DIE until everyone agrees to go home. Or rather, no one can escape DIE until everyone who is alive agrees to go home. The second arc of the [...] bleakly romantic fantasy fiction starts to reveal the secrets of the world, and our heroes' pasts. There's always the chance they'll escape DIE. They'll never escape themselves." --